2016
DOI: 10.1002/fsn3.385
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential of Juglans nigra, black walnut, husks extracted using supercritical carbon dioxide with an ethanol modifier

Abstract: The black walnut, Junglas nigra, is indigenous to eastern North America, and abscission of its fruit occurs around October. The fruit consists of a husk, a hard shell, and kernel. The husk is commonly discarded in processing, though it contains phenolic compounds that exhibit antioxidant and antimicrobial properties. For this study, black walnut husks were extracted using supercritical carbon dioxide with an ethanol modifier. The effects of temperature, ethanol concentration, and drying of walnut husks prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…It was observed that oil obtained by SC-CO 2 extraction had higher resistance against oxidation and higher radical scavenging activity compared to hexane extracted oil. Wenzel et al (2016) extracted phenolic compounds from black walnut (Juglans nigra) husks using SC-CO 2 with an ethanol modifier. The optimal extraction conditions were 68 °C and 20% ethanol in SC-CO 2 .…”
Section: Supercritical Fluid Extractionmentioning
confidence: 99%
“…It was observed that oil obtained by SC-CO 2 extraction had higher resistance against oxidation and higher radical scavenging activity compared to hexane extracted oil. Wenzel et al (2016) extracted phenolic compounds from black walnut (Juglans nigra) husks using SC-CO 2 with an ethanol modifier. The optimal extraction conditions were 68 °C and 20% ethanol in SC-CO 2 .…”
Section: Supercritical Fluid Extractionmentioning
confidence: 99%
“…In-situ extraction and impregnation of black walnut husk into polyethylene film using supercritical carbon dioxide with an ethanol modifier | 613 WENZEL Mikulic-Petkovsek, Slatnar, Veberic, Stampar, & Solar, 2011;Oliveira et al, 2008;Tabaraki & Rastgoo, 2014;Wang et al, 2015;Wenzel et al, 2016). Since walnut husks are commonly discarded, despite being a source of antioxidants, walnut husks present a potential for valorization.…”
Section: O R I G I N a L R E S E A R C Hmentioning
confidence: 99%
“…At these conditions, extracts were shown to exhibit antioxidant potential of 0.0554 mmol trolox equivalent/g of walnut using the ferric reducing ability of plasma (FRAP) assay and 7.13 mg gallic acid equivalent/g of walnut using the total phenolic content (TPC) assay (Wenzel et al, 2016). For extraction and impregnation, the mass loading of walnut husk with respect to ethanol content was varied from 0 to 1 g of walnut husk per gram of ethanol.…”
Section: In-situ Supercritical Carbon Dioxide and Ethanol Extractiomentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 The pericarp of walnut fruit (green husk) shows antioxidant, antiproliferative and antimicrobial activity. 14, [16][17][18][19] Since there has not been data on the antioxidant activity of walnut husk from the species naturally distributed in Sumadija region of Serbia, the aim of this paper was to determine its phenol and tannin content, antioxidant activity and to compare it to the current information available on antioxidant activity of walnut parts from other regions.…”
Section: Introductionmentioning
confidence: 99%